Non-collapsed Steady Ricci Solitons on a Cohomogeneity One-type Ansatz with a circle bundle over a product of Fano Kahler Einstein spaces as principal orbit - Mc Ginley, Dylan (My University, 2025)
We show a construction of Alexander Appleton giving new examples of non-collapsed non-Kahler steady Ricci solitons on a cohomogeneity one-type ansatz with principal bundle a line bundle over a single Fano Kahler Einstein base can be extended to the case where the base is a product of Fano Kahler Einstein manifolds.
Keywords: Riemannian Geometry; Geometric Analysis